Generalisable model development for fluid-inerter integrated damping devices. (July 2019) - Liu, Xiaofu; Titurus, Branislav; Jiang, Jason Zheng
Highlights: A generalisable model is developed for a selected fluid-inerter integrated damping (FID) design. The presented methodology is applicable to other FID device designs. A prototype helical-tube FID device was built for experimental testing. A bypass needle valve design is used to model the effect of piston valve damping with different opening sizes. The validity of the established generalisable model is verified by comparing the simulated dynamic response with the experimental results. Abstract: Vibration absorbers with a combination of stiffness, damping and inertance have been shown to be effective through numerous theoretical studies. One way to realise inertance is by using the fluid-based inerter, with the advantages of durability, structural simplicity and the similarity with existing damper constructions. Previous studies focused on accurate modelling of a specific fluid-based inerter device, while there has been no investigation on whether the dynamic models are still valid when its design parameters change. A model is termed here as being generalisable when it is able to sufficiently accurately characterise the terminal behaviour while allowing its design parameters to vary within their pre-defined ranges. In this paper, a generalisable model is developed for an example fluid-inerter integrated damping (FID) design. The methodology to develop such model uses the hydraulic and the corresponding mechanical networks representing the device, and tailored experimental testing to characterise each network element. Such approach is applicable to other design parameter settings and also other designs of FID devices.